Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1111/j.1528-1157.1999.tb00799.x
|View full text |Cite
|
Sign up to set email alerts
|

[18F]FDG‐PET and Whole‐Scalp MEG Localization of Epileptogenic Cortex

Abstract: Summary:Purpose: To evaluate combined [ I 'F]fluorodeoxyglucose ("F-FDG) positron emission tomography (PET) and 122-channel whole-scalp magnetoencephalography (MEG) in lateralizing the epileptogenic cortex in patients whose routine presurgical evaluations gave discordant results about the location of the epileptic focus.Methods: Nine patients (five women, four men) aged 13-40 years were studied. Subdural EEG (SEEG) was recorded from eight patients. Six patients were operated on.Results: In seven of nine patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 49 publications
0
24
0
1
Order By: Relevance
“…Spike localization by magnetoencephalography (MEG) has been compared with localization by intracranial EEG (2,(9)(10)(11)(12)(13)(14), positron emission tomography (PET) (15) and single-photon emission computed tomography (SPECT) (9). Previous studies suggested that the localization accuracy of MEG was higher than that of conventional scalp EEG (10,14) because of the absence of disturbance by the inhomogeneous conductivity of cranial tissues.…”
mentioning
confidence: 99%
“…Spike localization by magnetoencephalography (MEG) has been compared with localization by intracranial EEG (2,(9)(10)(11)(12)(13)(14), positron emission tomography (PET) (15) and single-photon emission computed tomography (SPECT) (9). Previous studies suggested that the localization accuracy of MEG was higher than that of conventional scalp EEG (10,14) because of the absence of disturbance by the inhomogeneous conductivity of cranial tissues.…”
mentioning
confidence: 99%
“…So far, only few studies addressed the question of the diagnostic yield of MEG, because most commonly only those patients who actually exhibited spikes on MEG were presented [29] or only patients with frequent interictal spikes on scalp EEG were referred for MEG recordings [30]. In one study where patients randomly selected from a presurgical epilepsy program were evaluated, epileptiform discharges on MEG could be recorded in 73% of cases [31].…”
Section: Diagnostic Yield Of Megmentioning
confidence: 99%
“…MEG source localizations showed good agreement with the ultimate localization of the epileptogenic zone in all three patients. In the study of Lamusuo et al [29], four patients with temporal lobe epilepsy and normal MRI scans were included. While MEG and PET yielded converging localizing evidence in these patients, no attempt was made to attribute MEG locations to subcompartments of the temporal lobe.…”
Section: Nonlesional Temporal Lobe Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect confirmation mainly comes from studies demonstrating co-localization with known epileptogenic substrates either visible on functional or structural imaging or confirmed with subsequent IC-EEG and successful surgical outcomes with supportive histopathology [7,10,11,13,15,16,18,[23][24][25][26][27][28][29][30].…”
Section: Magnetoencephalography Accuracy In Epilepsy Localizationmentioning
confidence: 99%